Identification of Whole-Serum Glycobiomarkers for Colorectal Carcinoma Using Reverse-Phase Lectin Microarray - Bertok, Tomas; Bertokova, Aniko; Jane, Eduard; Hires, Michal; Aguedo, Juvissan; Potocarova, Maria; Lukac, Ludovit; Vikartovska, Alica; Kasak, Peter; Borsig, Lubor; Tkac, Jan (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is one of the most common cancer type among men and women worldwide. There is a huge effort to discover novel and more cancer-specific biomarkers that could be detected in a non-invasive way. Analysis of aberrant glycosylation of serum glycoproteins is one way to the discovery of novel diagnostic and prognostic CRC biomarkers. In the present study, we investigated whole serum glycome with a panel of 16 different lectins in search of age-independent and CRC-specific glycomarkers using ROC analyses and glycan heat matrices. We identified glycosylation changes present in whole serum, which could lead to the discovery of novel biomarkers for CRC diagnostics. In particular, the change in the bisecting glycans (recognized by Phaseolus vulgaris erythroagglutinin) had the highest discrimination power for CRC diagnostics in combination with human L selectin providing AUC of 0.989 (95% CI 0.950-1.000), the specificity of 1.000, the sensitivity of 0.900 and the accuracy 0.960.